49.9k views
2 votes
Simplify: (2a2 - 3ab + 2b2) - (a2 + 2ab -5b2)

User Prp
by
4.8k points

1 Answer

5 votes

Answer:

a2 - 5ab + 7b2

Explanation:

Changes made to your input should not affect the solution:

(1): "b2" was replaced by "b^2". 3 more similar replacements.

= (((2•(a2))-3ab)+(2•(b2)))-(((a2)+2ab)-5b2)

= (((2•(a2))-3ab)+2b2)-(a2+2ab-5b2)

= ((2a2 - 3ab) + 2b2) - (a2 + 2ab - 5b2)

factor Into multi variable polynomial :

= 4.1 Factoring a2 - 5ab + 7b2

Your answer should be :

= a2 - 5ab + 7b2

User Himaan Singh
by
5.3k points